2005
DOI: 10.2223/jped.1402
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional injuries in the home environment: home safety

Abstract: Como citar este artigo: Paes CE, Gaspar VL. As injúrias não intencionais no ambiente domiciliar: a casa segura. J Pediatr (Rio J). 2005;81(5 Supl):S146-S154. AbstractObjective: To review the characteristics of unintentional injuries and their impact on children and adolescents. Sources of data:Articles published between 2000 and 2005 in the MEDLINE, EBSCO, Proquest, SciELO, BVS and Google Scholar databases were selected. The authors used the keywords unintentional injuries, injuries, safe home, burns, falls, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
1
7
0
4
Order By: Relevance
“…At first look, it might seem that employed mothers cannot dedicate adequate time to preventive measures because they spend less time at home; however, multivariate logistic regression analysis showed that the employment itself is not an independent factor for negative attitudes. Falls were the most common aetiologic factors for injuries in children referring to the treatment centres in the present study, consistent with the results of other studies (Eldosoky, 2012;Mack & Liller, 2010;Paes & Gaspar, 2005;United Nations International Children's Emergency Fund, 2002). However, apart from falls, other reasons too have been reported to be prevalent in other studies.…”
Section: Discussionsupporting
confidence: 93%
“…At first look, it might seem that employed mothers cannot dedicate adequate time to preventive measures because they spend less time at home; however, multivariate logistic regression analysis showed that the employment itself is not an independent factor for negative attitudes. Falls were the most common aetiologic factors for injuries in children referring to the treatment centres in the present study, consistent with the results of other studies (Eldosoky, 2012;Mack & Liller, 2010;Paes & Gaspar, 2005;United Nations International Children's Emergency Fund, 2002). However, apart from falls, other reasons too have been reported to be prevalent in other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Many other studies carried out in India and abroad also report falls as the commonest mode of injury. (4,5,14,15) In contrast to this a study done by Vani Madhavi Kommula. (10) reported that most common accidents reported were injuries from sharp or pointed instruments (32.2%) followed by falls (26.9%).…”
Section: Discussionmentioning
confidence: 88%
“…Children in particular are more vulnerable to domestic accidents, resulting in disability and loss of future productivity. (4,5) These accidents have not so far been recognized to the same extent as traffic and work-related injuries, largely because they have not been effectively counted.…”
Section: Introductionmentioning
confidence: 99%
“…Esses resultados são os primeiros obtidos no Brasil de um inquérito populacional sobre a ocorrência de acidentes em menores de cinco anos e estão em acordo com informações anteriormente disponíveis sobre acidentes como causas de óbitos e de hospitalizações no País . A preponderância de quedas também é encontrada tanto em estudos brasileiros como de outros países (BARACAT et al, 2000;GASPAR et al, 2004;PAES;GASPAR, 2005).…”
Section: // 185unclassified